(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
This article presents the findings of the HumanizAS Teaching Innovation Project, implemented in the “Introduction to Speech and Language Therapy” course at the University of Valladolid. Through semi-structured interviews conducted by students with professionals from various fields, the study analyzes narratives about training, vocation, working conditions, interdisciplinary coordination, and humanized care. The qualitative analysis using ATLAS.ti reveals that ethical values, empathy, and commitment are essential pillars in building person-centered speech and language therapy.